A Study on Seroprevalence of Hepatotropic Viruses in Neonatal Cholestasis Patients at a Tertiary Care Hospital of Central India - Nagaraj Perumal; Deepti Chaurasia; Rajeev Kumar Jain; Jyostna Srivastava (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Neonatal Cholestasis (NC) is defined as conjugated hyperbilirubinemia in infancy and diverse aetiologies and several disorders are responsible for this hepatobiliary dysfunction. Hepatotropic viral infection may have an important role in the pathogenesis of NC and related clinical outcomes. Aim: Hence, this study was aimed to estimate the seroprevalence of the hepatotropic viruses and their possible role in neonates presenting with cholestatic jaundice. Materials and Methods: This retrospective study included 51 infants who were presented with cholestatic jaundice. Serum samples were collected and screened for the hepatotropic viruses. The presence of serological markers to Cytomegalovirus (CMV), Epstein-Barr Virus (EBV), Hepatitis C (HCV), Hepatitis E (HEV), Herpes Simplex Virus (HSV) and Rubella were tested using enzyme-linked immunosorbent assays. Hepatitis B Virus (HBV) serostatus was determined by using rapid card tests. Results: Of the 51 cases, 4 (7.6%) patients presented with biliary atresia. Seroprevalence of CMV (23.5%) was found to be more predominant followed by EBV (13.7%), HCV (5.8%), HEV (5.8%), HSV (1.9%) and Rubella (1.9%). Co-infections were found in 7 (13.7%) cases and CMV-EBV co-infection being the most common. Conclusion: The presence of specific serological markers to hepatotropic viruses in the NC cases strongly suggests their aetiological role in this disorder. To the best of our knowledge, this is the first report documenting the seroprevalence of hepatotropic viruses in NC patients from Central India.